(3bUjOI jbhd GdYHO aj HOA GdCeGdjs - (3GdChTj, Ydj Hf YKeGf Hf eMeO, J HYO (B569 (3g`s ((3YKeGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; jbhd GdYHO aj HOA GdCeGdj dJhMjO HfXe cGddBdj (B- (3Edg GdNdb ehdGfG bOje hehUha HChUGa GdceGd (B- (3gh GdMj GdeOHQ cd CeQ gh GdMb GdebOQ Ph GdLdGds
(3BNQgG (B:s
(3hchfhG Yhf gPG GdYHO OgQG HPcQ GdNj aj MGd GHJgGd (B- (3dYd Gddg jYahg HaVd hjYWjg GdNjQ aj MGd GHJgGd (B- (3dYd Gddg jYahg HaVd hjYWjg GdSYGOI aj GdeBd (B- (3hEfj GdOgQ COYh cfg hSYj def HGdNjQ jheG bO OYGdjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 310s
(3eYLe GdeDdajf (B2 / 469s
(3cTa GdXfhf (B2 / 1349s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds